Kegagalan Sekulerisme: Solopos dan Representasi Agama di Media Massa - Muttaqin, Zaenal; Hikmawati, Ari; Na'imah, Elvi; Wedi, Agus (Academic Journal of Da'wa and Communication, 2023)
This paper examines the religious issues represented in secular media. Secularism has been regarded unavoidable since the development of science and technology and in line with positivistic idea. However, since the second half of the 20th century, sociologists of religion have argued that secularism is no longer relevant due to the insurgence of religions and religious institutions around the world. In particular, this paper discusses how Solopos –a newspaper in Surakarta- publishes articles related to the topics of religion. The research finds that even though Solopos is a secular media, it still publishes articles on religious issues. There is no specific policy regarding this publication, but it represents the contexts of the society that still regard religion as an important part of their life. Based on the research, this paper concludes that secularism has failed both in the public space such as media and in the mindset of the people of Surakarta.